2018
DOI: 10.1002/ijgo.12424
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiogenic factors in the pathogenesis and management of pre‐eclampsia

Abstract: The cause of pre-eclampsia is unknown. Different postulates have been developed to explain its pathogenesis. The two-stage theory and angiogenic imbalance are two notable postulates of the disease. Together, they propose that there is a lack of cytotrophoblastic invasion of the uterine spiral arteries in pre-eclampsia. The lumen of these arteries remains narrow instead of converting to the wide channels seen in normal pregnancy, and result in poor placental perfusion. Coupled with maternal susceptibility, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 44 publications
1
53
0
7
Order By: Relevance
“…This means when MgSO 4 is used for reducing maternal high blood pressure, vasorelaxation effects by the drug are relatively weaker in the placenta, which may benefit the maintenance of placental vascular tension for a sufficient local perfusion and circulation. Notably, a number of studies reported that preeclampsia is accompanied by poor placental perfusion and ischemia 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…This means when MgSO 4 is used for reducing maternal high blood pressure, vasorelaxation effects by the drug are relatively weaker in the placenta, which may benefit the maintenance of placental vascular tension for a sufficient local perfusion and circulation. Notably, a number of studies reported that preeclampsia is accompanied by poor placental perfusion and ischemia 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelial growth factor (VEGF) is proangiogenic factor mostly synthesized by endothelial cells, macrophages, T-cells, tumor cells and cytothrophoblast in response to stimulation by hypoxia or various mediators (interleukins, transforming growth factor β -TGF-β, platelet derived growth factors) (45). There are five members of VEGF family in mammals, VEGF-A, VEGF-B, VEGF-C, VEGF-D and placental growth factor (PlGF).…”
Section: Angiogenic Factors In Preeclampsiamentioning
confidence: 99%
“…Centralnym elementem w badaniu etiologii preeklampsji jest łożysko, gdyż jak wiadomo rozwiązanie ciąży i usunięcie łożyska jest konieczne w celu zlikwidowania objawów choroby [43,44]. Badanie łożyska pochodzącego od kobiet z zaawansowanym stanem preeklampsji pokazało, że występują w nim zwężone tętniczki oraz liczne obszary charakteryzujące się martwicą niedokrwienną [45].…”
Section: Patogeneza Preeklampsjiunclassified